Forests, Lived Relations, and Dance Creation in Papua - Ida Bagus Gede Surya Peradantha; Andy McNeilly; Jimmi Rerei; Yosinta Kawagop; Dominggas Sobi; Kadek Indra Wijaya; Ellaboge Mulyani Uaga (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study explains how forests are positioned as living spaces within Papuan worldviews and how disruptions to this relationship affect sources of artistic creation, particularly dance. The study adopts a conceptual approach grounded in literature synthesis, critical engagement with previous scholarship, and contextual reflection on cultural and artistic practices. The analysis shows that forests are understood as living spaces that shape sociocultural relations, cosmological orientations, and embodied experience among Papuan communities, while sustaining the continuity of cultural practice and dance creation. Disruptions such as pollution, deforestation, and land conversion affect not only physical ecology but also interrupt lived practices, embodied knowledge, and cultural meanings that underpin creative processes. The study clarifies that forests are not treated as a singular origin of Papuan dance but as one of several relational spaces within a network of lived experience that informs artistic creation. These findings contribute to performing arts scholarship by framing the forest as a relational and epistemic foundation for dance creation and by offering conceptual implications for creative practice and context-based choreographic education.